Percepção dos gestores sobre o desempenho do portfólio advinda da utilização de métodos de avaliação e seleção de portfólio de projetos de PD&I: um estudo de caso nos institutos LACTEC - Durães, Andrea Gui Knopfholz (2014)
The purpose of this study was to assess managers´ perceptions of portfolio performance derived from the use of RD&I projects portfolio assessment and selection methods in a science, technology and innovation institutions, in the period between 2008 and 2013. For such, the case study method was chosen, which included interviews with key managers involved in portfolio management. The field research and its results were based on a theoretical framework, having as its main approach the projects portfolio prioritization field. The LACTEC institutes used financial methods in their assessment and selection of RD&I projects portfolio, and methods proposed by ANEEL programs. It follows that the participation of the LACTEC institutes in each ANEEL program is guided by criteria that involve the use of more than one RD&I project assessment and selection method, which demonstrates that the LACTEC institutes stand as institutions provided with strong and creative managerial capability to present a consistent portfolio. Therefore, the study demonstrated that the managers´ perception of the importance of the methods used points to the need to develop clear RD&I projects portfolio management methodologies, if they are to reach the objectives and goals proposed by strategic planning and thus be able to maximize results.